Evaluation of Vector Competence of Ixodes Ticks for Kemerovo Virus - Camille Victoire Migné; Hélène Braga de Seixas; Aurélie Heckmann; Clémence Galon; Fauziah Mohd Jaafar; Baptiste Monsion; Houssam Attoui; Sara Moutailler (Viruses, 2022)
Tick-borne viruses are responsible for various symptoms in humans and animals, ranging from simple fever to neurological disorders or haemorrhagic fevers. The Kemerovo virus (KEMV) is a tick-borne orbivirus, and it has been suspected to be responsible for human encephalitis cases in Russia and central Europe. It has been isolated from Ixodes persulcatus and Ixodes ricinus ticks. In a previous study, we assessed the vector competence of I. ricinus larvae from Slovakia for KEMV, using an artificial feeding system. In the current study, we used the same system to infect different tick population/species, including I. ricinus larvae from France and nymphs from Slovakia, and I. persulcatus larvae from Russia. We successfully confirmed the first two criteria of vector competence, namely, virus acquisition and trans-stadial transmission, for both tick species that we tested. The estimated infection rates of engorged and moulted ticks suggest specificities between viral strains and tick species/developmental stages.